2021
DOI: 10.1186/s12909-021-02508-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blended learning on learning outcomes in the public healthcare education course: a review of flipped classroom with team-based learning

Abstract: Background A flipped classroom with team-based learning is a blended educational strategy that guides active learning inside and outside the classroom. This study aimed to verify the effects of this innovative blended educational strategy on knowledge, problem-solving ability, and learning satisfaction of undergraduate nursing students undergoing public healthcare education. Methods The subjects were undergraduate nursing students enrolled in H Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 40 publications
(44 reference statements)
4
32
0
2
Order By: Relevance
“…While change implementation can be challenging, the team found that aligning individual projects to the strategic goals of the organization and recognizing the voices of all the customers affected by the project is essential to sustaining LSS [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The team ensured to include key stakeholders to include: Chief Operations Officer, Director of Human Resources, Director of Nursing, Assistant Director of Nursing, Director of Education, members of the Education Department, and Clinical facilitators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While change implementation can be challenging, the team found that aligning individual projects to the strategic goals of the organization and recognizing the voices of all the customers affected by the project is essential to sustaining LSS [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. The team ensured to include key stakeholders to include: Chief Operations Officer, Director of Human Resources, Director of Nursing, Assistant Director of Nursing, Director of Education, members of the Education Department, and Clinical facilitators.…”
Section: Discussionmentioning
confidence: 99%
“… Introduction of a Blended Learning Method (BLM) of BLS Heartcode training. BLS Heartcode is a self-directed, comprehensive eLearning program that uses adaptive learning technology to allow learners to acquire and demonstrate BLS Skills with a personalized learning path that adapts to the individual learner’s performance [ 50 , 51 , 52 , 53 , 54 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Engelbertink et al [26] found that the participatory design approach to leading BL course is the use of technology that focuses on content, target group, context, and ethical aspects in the course. Kang et al [27] verify a flipped classroom on knowledge, problem-solving, and satisfaction student in designing BL. Ayob et al [28] identify the effectiveness of using the strategy of BL toward higher students in the United Arab Emirates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It allows students to move beyond the nearest development zone to a higher level. Based on the learning of this theory, the structure diagram of the flipped classroom combined scenario simulation teaching relationship based on big data is given, as shown in Figure 2: 3 Wireless Communications and Mobile Computing necessary to understand the characteristics of big data technology so as to give full play to its strengths and advantages [22]. Big data technology can process a huge amount of data.…”
Section: Theoretical Basis Of Flipped Classroom Combined Withmentioning
confidence: 99%